Modern perspectives on the gold standard - Bayoumi, Tamim A.; Eichengreen, Barry J.; Taylor, Mark P., 1958- (Cambridge : Cambridge University Press, 1996)
Currency crises in Europe and Mexico during the 1990s provided stark reminders of the importance and the fragility of international financial markets. These experiences led some commentators to conclude that open international capital markets are incompatible with financial stability. But the pre-1914 gold standard is an obvious challenge to the notion that open capital markets are sources of instability. To deepen our understanding of how this system worked, this volume draws together recent research on the gold standard. Theoretical models are used to guide qualitative discussions of historical experience, while econometric methods are used to help the historical data speak clearly. The result is an overview of the gold standard, a survey of the relevant applied research in international macroeconomics, and a demonstration of how the past can help to inform the present.
Modern perspectives on the gold standard: introduction / Tamim Bayoumi, Barry Eichengreen, and Mark P. Taylor -- Unit roots, shocks, and VARs and their place in history: an introductory guide / Terence C. Mills -- The gold standard as a commitment mechanism / Michael D. Bordo and Finn E. Kydland -- Market efficiency and regime efficiency under the 1925-1931 dollar/sterling gold standard / Lawrence H. Officer -- Credibility and fundamentals: were the classical and interwar gold standards well-behaved target zones? / C. Paul Hallwood, Ronald McDonald, and Ian W. Marsh -- The stability of the gold standard and the evolution of the international monetary fund system / Tamim Bayoumi and Barry Eichengreen -- International adjustments under the classical gold standard: evidence from the United States and Britain, 1879-1914 / Charles W. Calomiris and R. Glenn Hubbard -- Balance of payments adjustment under the gold standard policies: Canada and Australia compared / Trevor J.O. Dick, John E. Floyd and David Pope -- Money demand and supply under the gold standard: the United Kingdom, 1870-1914 / Forrest H. Capie and Geoffrey E. Wood -- Stability and forward-looking behavior: the demand for broad money in the United Kingdom, 1871-1913 / Mark P. Taylor and Geoffrey E. Wood -- The dollar/pound real exchange rate and fiscal policy during the gold standard period / Graciela L. Kaminsky and Michael Klein -- Exchange rate dynamics and monetary reforms: theory and evidence from Britain's return to gold / Panos Michael, A. Robert Nobay, and David A. Peel -- Déja vu all over again: lessons from the gold standard for European monetary unification / Barry Eichengreen.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Gold standard